Waist-to-hip ratio, body mass index and hypertension among adults in the San Rafael catchment area in Miag-ao, Iloilo - Alfabeto, Ace Robert; Anglopez, Mae Therese (2009.)
The study determined the relationship of anthropometric measures Body Mass Index and Waist to hip ratio with hypertension. Several biological and socio-demographic variables including age, physical activitiy, family history, family income, smoking and alcohol consumption were studied to determine their possible association with hypertension. These were analyzed with binary logistic regression for their possible association with hyperstension
Research Paper (Undergraduate, Bachelor of Science in Public Health) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Hypertension -- San Rafael, Miagao, Iloilo; Body Mass Index -- San Rafael, Miagao, Iloilo